Perilaku Agresi akibat Problematic Social Media Use dan Peran Social Support sebagai Moderator - Lorenza Dia Prameswari; Dyan Evita Santi; Rahma Kusumandari (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2026)
Adolescents are individuals in a crucial stage of social development, where they tend toengage and interact with their social groups to develop social skills. However, such intense social interactions may also lead to interpersonal conflicts, which have the potential to trigger aggressive behavior. This study aims to examine the moderating role of social support in the relationship between problematic social media use and aggressive behavior among adolescents. The research employed a quantitative correlational method with a total of 377 university students selected through accidental sampling. The instruments used included an aggression scale adapted from Buss & Perry (1992) with a reliability of 0.959, a problematic internet use scale from Caplan (2010) with a reliability of 0.954, and a social support scale from Sarafino and Smith (2011) with a reliability of 0.944. Data analysis was conducted using Pearson Product Moment correlation. The results showed that social support significantly moderates the relationship between problematic social media use and aggressive behavior. High levels of social support were found to reduce tendencies toward aggressive behavior, even when individuals experienced problematic social media use. Therefore, social support serves as a protective factor for adolescents.Keywords: Adolescents, Aggressive Behavior, Problematic Social Media Use, Social Support Remaja merupakan individu yang sedang berada pada tahap perkembangan sosial yang penting, di mana mereka cenderung berinteraksi dan bergabung dengan kelompok sosialnya untuk mengembangkan keterampilan sosial. Namun, interaksi sosial yang intens ini juga dapat menimbulkan konflik dalam hubungan interpersonal, yang berpotensi memicu perilaku agresi. Penelitian ini bertujuan untuk menguji peran moderasi social support dalam hubungan antara problematic social media use dan perilaku agresi pada remaja. Penelitian menggunakan metode kuantitatif korelasional dengan jumlah responden sebanyak 377 mahasiswa yang dipilih menggunakan teknik accidental sampling. Instrumen yang digunakan meliputi skala perilaku agresi yang diadaptasi dari Buss & Perry (1992) dengan reliabilitas 0,959, skala problematic internet use dari Caplan (2010) dengan reliabilitas 0,954, dan skala social support dari Sarafino dan Smith (2011) dengan reliabilitas 0,944. Teknik analisis data yang digunakan adalah korelasi Pearson Product Moment. Hasil penelitian menunjukkan bahwa social support mampu memoderasi secara positif hubungan antara problematic social media use dan perilaku agresi. Dukungan sosial yang tinggi terbukti dapat mengurangi kecenderungan perilaku agresi meskipun individu mengalami penggunaan media sosial yang bermasalah, sehingga social support berperan sebagai faktor pelindung bagi remajaKata kunci: Perilaku Agresi, Problematic Social Media Use, Remaja, Social Support